SINTESIS KATALIS ABU SEKAM PADI TERIMPREGNASI DENGAN CaO DARI CANGKANG TELUR DAN KOH UNTUK PEMBUATAN BIODIESEL DARI MINYAK JELANTAH : SINTESIS KATALIS ABU SEKAM PADI TERIMPREGNASI DENGAN CaO DARI CANGKANG TELUR DAN KOH UNTUK PEMBUATAN BIODIESEL DARI MINYAK JELANTAH - Ainirahmah Ismaraniah Nurhasyiri; Mustain; Anerasari Mediniariasty (KINETIKA, 2022)
Rice husk ash (RHA) produced from combustion at high temperatures has the main composition of silica (SiO2) which makes ASP as a potential catalyst support in the triglyceride transesterification process to increase the activity of CaO catalyst. CaO is one of the most popular types of heterogeneous catalysts because it is easily found in nature such as egg shells. Because CaO has drawbacks such as low reaction rate, easy reaction with air, and leaching, which reduces its catalytic activity and reduces biodiesel yield, for this reason, it is necessary to insert alkali metals such as K from KOH and rice husk ash as support. This study aims to obtain heterogeneous CaO/KOH/ASP catalysts with high catalytic activity, determine the optimal ratio of CaO/KOH/ASP catalysts and determine its characterization based on the yield and quality of biodiesel produced and produce biodiesel that meets SNI. In this research, the catalyst manufacture was carried out using the wet impregnation method, where the mass of CaO:ASP with varying masses (0:10, 2.5:7.5; 5:5; and 7.5:2.5) was immersed in a KOH solution which was also varied. concentrations are 25%, 30%, and 35%. The catalyst was then calcined to be activated and tested in the manufacture of biodiesel. In this study, a catalyst with high catalytic activity was obtained with the optimum ratio at CaO:ASP 2.5:7.5 and KOH 25%, where the biodiesel yield obtained was 94.62% with a density of 0.876 gr/ml, viscosity 3.75 cSt, flash point 151.10C, cetane number 66.99 and methyl ester content of 96.21%. The quality of biodiesel produced has complied with SNI.